Characterizing marijuana concentrate users: A web-based survey - Daniulaityte, R.; Lamy, F.; Barratt, Monica; Nahhas, R.; Martins, S.; Boyer, E.; Sheth, A.; Carlson, R. (Elsevier Ireland Ltd, 2017)
The study seeks to characterize marijuana concentrate users, describe reasons and patterns of use, perceived risk, and identify predictors of daily/near daily use. Methods An anonymous web-based survey was conducted (April-June 2016) with 673 US-based cannabis users recruited via the Bluelight.org web-forum and included questions about marijuana concentrate use, other drugs, and socio-demographics. Multivariable logistic regression analyses were conducted to identify characteristics associated with greater odds of lifetime and daily use of marijuana concentrates. Results About 66% of respondents reported marijuana concentrate use. The sample was 76% male, and 87% white. Marijuana concentrate use was viewed as riskier than flower cannabis. Greater odds of marijuana concentrate use was associated with living in states with “recreational” (AOR = 4.91; p = 0.001) or “medical, less restrictive” marijuana policies (AOR = 1.87; p = 0.014), being male (AOR = 2.21, p = 0.002), younger (AOR = 0.95, p < 0.001), number of other drugs used (AOR = 1.23, p < 0.001), daily herbal cannabis use (AOR = 4.28, p < 0.001), and lower perceived risk of cannabis use (AOR = 0.96, p = 0.043). About 13% of marijuana concentrate users reported daily/near daily use. Greater odds of daily concentrate use was associated with being male (AOR = 9.29, p = 0.033), using concentrates for therapeutic purposes (AOR = 7.61, p = 0.001), using vape pens for marijuana concentrate administration (AOR = 4.58, p = 0.007), and lower perceived risk of marijuana concentrate use (AOR = 0.92, p = 0.017). Conclusions Marijuana concentrate use was more common among male, younger and more experienced users, and those living in states with more liberal marijuana policies. Characteristics of daily users, in particular patterns of therapeutic use and utilization of different vaporization devices, warrant further research with community-recruited samples.